Assessment of provider attitudes toward #naloxone on Twitter. Issue 1 (2nd January 2016) - Haug, Nancy A.; Bielenberg, Jennifer; Linder, Steven H.; Lembke, Anna
ABSTRACT: Background : As opioid overdose rates continue to pose a major public health crisis, the need for naloxone treatment by emergency first responders is critical. Little is known about the views of those who administer naloxone. The current study examines attitudes of health professionals on the social media platform Twitter to better understand their perceptions of opioid users, the role of naloxone, and potential training needs. Methods : Public comments on Twitter regarding naloxone were collected for a period of 3 consecutive months. The occupations of individuals who posted tweets were identified through Twitter profiles or hashtags. Categories of emergency service first responders and medical personnel were created. Qualitative analysis using a grounded theory approach was used to produce thematic content. The relationships between occupation and each theme were analyzed using Pearson chi-square statistics and post hoc analyses. Results : A total of 368 individuals posted 467 naloxone-related tweets. Occupations consisted of professional first responders such as emergency medical technicians (EMTs), firefighters, and paramedics ( n = 122); law enforcement officers ( n = 70); nurses ( n = 62); physicians ( n = 48); other health professionals including pharmacists, pharmacy technicians, counselors, and social workers ( n = 31); naloxone-trained individuals ( n = 12); and students ( n = 23). Primary themes included burnout, education and training, information seeking, news updates, optimism, policy and economics, stigma, and treatment. The highest levels of burnout, fatigue, and stigma regarding naloxone and opioid overdose were among nurses, EMTs, other health care providers, and physicians. In contrast, individuals who self-identified as "naloxone-trained" had the highest optimism and the lowest amount of burnout and stigma. Conclusions : Provider training and refinement of naloxone administration procedures are needed to improve treatment outcomes and reduce provider stigma. Social networking sites such as Twitter may have potential for offering psychoeducation to health care providers.